2021
DOI: 10.3390/biom11040562
|View full text |Cite
|
Sign up to set email alerts
|

Role of Thrombin in Central Nervous System Injury and Disease

Abstract: Thrombin is a Na+-activated allosteric serine protease of the chymotrypsin family involved in coagulation, inflammation, cell protection, and apoptosis. Increasingly, the role of thrombin in the brain has been explored. Low concentrations of thrombin are neuroprotective, while high concentrations exert pathological effects. However, greater attention regarding the involvement of thrombin in normal and pathological processes in the central nervous system is warranted. In this review, we explore the mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 233 publications
0
28
0
Order By: Relevance
“…Unexpectedly, thrombin activation slightly increased at 7 dpi compared with 3 dpi. We suspect that the increase of thrombin during the subacute stage may have a protective effect on neural injury, on account of evidence shown its neural protective effect with low concentration [ 50 ]. Hence, the strange thrombin activation upregulation of thrombin activation at the subacute stage after SCI remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, thrombin activation slightly increased at 7 dpi compared with 3 dpi. We suspect that the increase of thrombin during the subacute stage may have a protective effect on neural injury, on account of evidence shown its neural protective effect with low concentration [ 50 ]. Hence, the strange thrombin activation upregulation of thrombin activation at the subacute stage after SCI remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that in other CNS disorders active thrombin might play a role. 56 These disorders include, but are not limited to, focal cerebral ischemia (ischemic stroke), intracerebral hemorrhage (ICH), 57 arteriovenous malformations (AVMs), 58 multiple sclerosis (MS), 59 germinal matrix hemorrhage, 60 intracerebral hemorrhage due to hypertension, 61,62 traumatic brain injury, 63 and CNS neoplasms. 64 To our knowledge at this time the ability of thrombin to degrade cerebral vascular components has not been studied in those disorders or their model systems.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence supports key roles of complement and coagulation in the neuroinflammatory damage induced following stroke, neoplasms, epilepsy, traumatic brain and nerve injury, and neurodegenerative diseases [ 73 , 141 , 142 ]. Coagulation and inflammation are well-known to interact with each other in both physiological and pathophysiological states of the nervous system [ 14 , 46 , 113 , 143 ].…”
Section: Discussionmentioning
confidence: 99%